The impact of diabetes mellitus on tuberculosis recurrence in Eastern China: a retrospective cohort study - Yuting Wang; Jinyan Shi; Xiwen Yin; Bilin Tao; Xinling Shi; Xinlan Mao; Qin Wen; Yuan Xue; Jianming Wang (BMC, 2024)
Abstract Background The comorbidity of tuberculosis (TB) and diabetes mellitus (DM) is a significant global public health issue. This study aims to explore the recurrence risk and related factors of active pulmonary TB, specifically focusing on the impact of DM. Methods A retrospective cohort study was conducted in Lianyungang City, Jiangsu Province, Eastern China by recruiting 12,509 individuals with newly diagnosed pulmonary TB between 2011 and 2019. The Cox proportional hazards models were performed to identify risk factors of recurrence and assess the association between DM and recurrence. The hazard ratio (HR) and 95% confidence interval (CI) were used to estimate the strength of the association. Results After a median follow-up period of 5.46 years, we observed 439 recurrent cases (incident recurrence rate: 6.62 per 1000 person-years). Males (HR: 1.30, 95% CI: 1.03-1.64), patients aged ≥ 60 years (HR: 1.39, 95% CI: 1.15-1.70), DM (HR: 2.40, 95% CI: 1.68-3.45), and etiologic positivity in the initial episode (HR: 2.42, 95% CI: 2.00-2.92) had a significantly increased risk of recurrence. Conclusions Recurrence of pulmonary TB patients who have completed treatment, especially those who also suffer from DM, should be a concern. Enhanced follow-up and targeted surveillance of these high-risk groups are needed.